Performance of Funds of Funds in Brazil - Borges Junior, Dermeval Martins (2018)
Among the modalities of existing funds are the Investment Funds in Quotas (FICs), which they are funds that acquire shares from other funds instead of directly investing in market assets. In addition to offering the inherent advantages of traditional funds, the FIC allows the expansion of investment options, since its structure allows access to several other funds with low initial investment. On the other hand, the structure of the FICs presents rates and costs that can negatively affect their performance. However, the objective of this study is to analyze the performance of the Brazilian FICs, with focus on the other funds. From a sample of 1,723 stock funds, with data available for the period from January 2005 to March 2016, the analysis was used to reach the objective of the study. The results indicated better performance indicators (Sharpe Ratio) for FICs, compared to the other funds in the sample.